Comprehensive resource for transcription readthrough events in healthy human tissues - Yang Mei; Ziqi Cheng; Yueqi Lu; Shiyi Wu; Xi Chen (Scientific Data)
Abstract Transcription readthrough occurs when RNA polymerase bypasses canonical termination sites, producing elongated RNA molecules called readthrough (RT) transcripts or downstream of gene (DoG) transcripts. Although RT transcripts have been implicated in stress responses and pathological states, their roles in healthy human tissues are poorly understood. This study collected and analyzed RT events across 43 healthy human tissues, identifying 75,248 RT events from 35,720 transcripts across 11,692 genes. The dataset encompasses the sequences, locations, expression profiles, and comprehensive annotation information of corresponding genes for RT transcripts. It provides a thorough elucidation of RT transcriptomics and its significance in gene regulation, offering a wealth of benchmark data to facilitate further research on RT transcripts.